REINFORCING STRUCTURE FOR UNDERGROUND CAVITY AND REINFORCING METHOD - IZUMI AKIHIKO; MITSUI TATSUYA (2021)
To provide a reinforcing structure and a reinforcing method that can reliably reinforce the underground cavity by preventing the fluidized soil from leaking out of a bag and by allowing the fluidized soil to push the bag well apart, since the bag is not easily damaged by the fluidized soil.SOLUTION: The present invention comprises a hole forming step of forming a through hole 6 that vertically leads to an underground cavity 5 in a ground surface layer portion 3 on the underground cavity 5, a bag body arranging step in which an impermeable bag 11 connected under a hose 12 is placed in the underground cavity 5 through the through hole 6 in a folded state, a soil filling step of filling the bag 11 with a fluidized soil 14 sent from the hose 12, a soil hardening step of hardening the fluidized soil 14. At least a part of the underground cavity is reinforced with a soil-containing bag 15 formed by filling the bag 11 with fluidized soil 14 and hardening it.SELECTED DRAWING: Figure 6 【課題】袋体が流動化処理土によって傷みにくいため、流動化処理土が袋体から漏れず、流動化処理土が袋体をよく押し広げて、地中空洞を確実に補強することができる補強構造及び補強方法を提供する。【解決手段】地中空洞５上の地盤表層部３に地中空洞５へ縦方向に通じる通孔６を形成する通孔形成工程と、ホース１２の下に接続した不透水性の袋体１１を折り畳んだ状態で通孔６を通して地中空洞５に配置する袋体配置工程と、前記袋体１１にホース１２から送った流動化処理土１４を充填する土充填工程と、前記流動化処理土１４を硬化させる土硬化工程とを含み、地中空洞の少なくとも一部を、前記袋体１１に流動化処理土１４が充填し硬化してなる土入り袋体１５で補強する。【選択図】図６